The Effect of Project-Based Learning Assisted by Electronic Media on Learning Motivation and Science Process Skills - Safaruddin Safaruddin; Nurlaiha Ibrahim; Juhaeni Juhaeni; Harmilawati Harmilawati; Laeli Qadrianti (Yayasan Keluarga Guru Mandiri, 2020)
This study aims to analyze the effect of using Project Based Learning (PjBL) strategy assisted by Electronic Media in increasing learning motivation and Science Process Skills (KPS) on the material “Heat Transfer”. The study used a quasi-experimental pretest-posttest experimental design with 59 students. The experimental group was taught using the PjBL strategy while the control group was taught with a conventional strategy that was teacher-centred. Learning motivation is measured using questionnaires distributed to students, and KPS is measured through observation using observation sheets. The results, average score of KPS with the PjBL strategy = 86.33, the conventional strategy = 74.52; the average score of learning motivation with PjBL strategy = 78.05, conventional strategy = 69.49. Conclude from this data that the use of the PjBL based on e-media strategy is effective and influences the improvement of KPS and learning motivation of elementary school students.